2019
DOI: 10.1093/jas/skz087
|View full text |Cite
|
Sign up to set email alerts
|

Generalized additive mixed model on the analysis of total transport losses of market-weight pigs1

Abstract: Transportation losses of market-weight pigs are an animal welfare concern, and result in direct economic impact for producers and abattoirs. Such losses are related to multiple factors including pig genetics, human handling, management, and weather conditions. Understanding the factors associated with total transport losses (TTL) is important to the swine industry because it can aid decision-making, and help in the development of transportation strategies to minimize the risk of losses. Hence, the objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Total transport losses (DOAs and non-ambulatory pigs) were associated with the truck driver in this study. Similar results were reported by Passafaro et al ( 58 ) Who found that transport losses were lower when trucks were driven by owners rather than employees, because owners have a vested interest and therefore are more careful in handling and moving pigs throughout the transport process, compared to hired drivers. Other researchers have reported that the level of knowledge in pig behavior and the handling skills of drivers directly influences animal welfare ( 26 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Total transport losses (DOAs and non-ambulatory pigs) were associated with the truck driver in this study. Similar results were reported by Passafaro et al ( 58 ) Who found that transport losses were lower when trucks were driven by owners rather than employees, because owners have a vested interest and therefore are more careful in handling and moving pigs throughout the transport process, compared to hired drivers. Other researchers have reported that the level of knowledge in pig behavior and the handling skills of drivers directly influences animal welfare ( 26 ).…”
Section: Discussionsupporting
confidence: 87%
“…Many factors have been associated with the effect of the driver on animal welfare such as: attitude and empathy toward animals ( 32 , 60 ), years of experience as a truck driver ( 29 ), work pressure and interpersonal relationships training ( 59 ), coaching and driving style, among others ( 45 ). These results suggest that understanding in greater depth the differences between drivers may further explain transportation losses, and therefore be useful to the swine industry to contract, hire, or train truck driver ( 58 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Demographic and clinicopathologic data at biopsy were obtained from our IgAN database. The following baseline covariates were analyzed in the multivariable models as they were potential confounders for the progression of renal damage (the generalized additive mixed model [GAMM] 28 automatically included the initial eGFR as a covariate): age, gender, mean artery pressure (MAP, calculated as 1/3 × systolic blood pressure [SBP] + 2/3 × diastolic blood pressure [DBP]), proteinuria (measured using 24 h urine protein excretion [g/d]), and the Oxford Classification MEST-C score.…”
Section: Methodsmentioning
confidence: 99%
“…GAMMs were used to investigate the fixed effects of the Oxford Classification of M, E, S, T, and C associations with longitudinal changes in eGFR. 28 In these models, the dependent variable (eGFR) was evaluated at the baseline visit and during all follow-up visits, whereas the independent variables were only assessed at the baseline visit (Oxford Classification scores M, E, S, T, and C). Age, gender, MAP, proteinuria, and the Oxford Classification MEST-C score were adjusted in the multivariable models to determine whether the effects of M, E, S, T, and C on the changes in eGFR were independent.…”
Section: Methodsmentioning
confidence: 99%